Hemimandibulectomy of an extensive complex odontoma in the mandible: a case report - retno widayanti; Winarno Priyanto; Kiki A. Rizki; Andri Hardianto (DiscoverSys Inc., 2017)
Objective: Odontomas are the most common form of odontogenic tumors of the jaw, represent a benign hamartoma rather than a true neoplasm. They constitute 22% of all odontogenic tumors. Odontomas are consist of two types, compound and complex. The compound odontomas contain recognizable enalmel, dentin and sometimes cementum, shaped in toothlike structures; whereas complex odontomas are composed of irregular masses of dentin and enamel and have no anatomic resemblance to a tooth.Methods: A17-year-old female patient came to Department of Oral and Maxillofacial Surgery with a slow growing and asymptomatic swelling in her left mandible. The panoramic radiograph showed a radioopacity and radiolucent lesion, with well-corticated limits. The radioopaque area was amorphous, circumscribed by a thin and irregular radiolucent halo. An inscisional biopsy confirmed the lesion as a complex odontoma. The surgery performed was hemimandibulectomy followed by a reconstruction using a plate under general anaesthesia.Results: Complex odontomas are most likely to be found in the posterior region of the maxilla or the mandible and can be treated with a simple enucleation and curettage. In this case report the hemimandibulectomy was performed due to the extensiveness of the mass.Conclusion: Surgical removal of large complex odontoma with hemimandibulectomy is a rare clinical scenario. The extensiveness of the lesion contributed to its removal technique.